Sustainable Processes for the Removing of Heavy Metals from Aqueous Solutions - Palet, Cristina; Bastos-Arrieta, Julio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This article collection from the Special Issue "Sustainable Processes for the Removing of Heavy Metals from Aqueous Solutions" attempts to summarize the state-of-the-art of current macro-, micro- and nanotechnologies for water purification, discussing their field of application, especially for heavy-metal ion removal. For instance, it presents the recently available information on utilizing different biomass materials for heavy metals removal, highlighting the increasing use of these materials due to their low cost, regeneration ability, high adsorption efficiency, and small chemical or biological sludge with a possibility of metal recovery.